Online Theme Landscaping Decision Support System - Hassan, N.; Mohmad Hassim, Y.M.; Afip@Afif, Z.A.; Suan, S.E. (Journal of Engineering and Technology (JET), 2011)
The landscape theme has become an important feature for home exterior design. However, selecting a landscape theme based on client preference is difficult due to multiple criteria and budget constraint during the selection process. This paper proposed online decision support systems for selecting landscape theme design that can be use by exterior designer consultant in assisting home owner to make decision within their own budget range. This prototype is constructed using a decision tree as an analysis tool. This online application was developed using PHP as programming language and mySQL as the database platform. This system may not provide the best theme but it will assist the home owner in deciding which one of the design concepts is most suitable according to their needs and preferences.